Propriedades físico-químicas e mecânicas, potencial bioativo e caracterização da interface dentina-cimento de cimentos endodônticos experimentais à base de cimento Portland associados à radiopacificadores micro e nanoparticulados - Viapiana, Raqueli [UNESP] (2014)
Portland Cement is composed by calcium silicate and the association with additives or vehicles, may confer characteristics to enable the use of this cement as root canal sealer. However, Portland cement lacks in radiopacity which requires the addition of a radiopacifying agent to the mixture to be used as dental material. The purpose of this study was to assess the physicochemical and mechanical properties, the bioactivy potential and to characterize the dentin-sealers interfaces of Portland-based experimental root canal sealers (ES) containing nano or micro particles of zirconium oxide or niobium oxide. Setting time, compressive strength, flow ability, film thickness, radiopacity, solubility and dimensional stability were evaluated according to ISO 6876:2012 standards, whereas formaldehyde realease was investigated using gas-cromatography. Dentin bond strength was evaluated by push-out test and the sealer’s microestruture and bioactivity potential were perfomed using X-ray energy espectroscopy, X-ray diffractometry and infrared spectroscopy. Dentin-sealers interface was assessed with respect to fluorescent microspheres penetration and it was also examined using confocal microscope and scanning electron microscope coupled to X-ray energy dispersive line scans. Data were analyzed by ANOVA and Tukey post-hoc test (p < 0.05). With the exception of radiopacity, ES showed physicochemical properties according to ISO 6876:2012 specifications, adequate dentin bond strength, great bioactivity potential and promoted coronal sealing and chemical interaction with dentin.